Avaliação clínica, genética, radiológica e da arquitetura retiniana em pacientes com ataxia relacionada ao gene SACS - Rezende Filho, Flavio Moura [UNIFESP] (2019)
BACKGROUND: Cerebellar ataxia is characterized by loss of balance and coordination, and is found in several neurological conditions. This group of disorders is very diverse in clinical presentations and etiopathogenesis, and includes neurovascular, inflammatory, infectious, neurodegenerative and hereditary diseases. Genetic defects are an important cause of ataxia. The progress in molecular diagnosis techniques has allowed the identification of causative genes and characterization of new forms of ataxia, including the autosomal recessive spastic ataxia of CharlevoixSaguenay (ARSACS), described in 1978 in French-Canadian families. The causative gene of this disorder, SACS, was identified in 2000 and this allowed molecular confirmation in several regions of the world. Thickening in the retinal nerve fiber layer (RNFL) in optical coherence tomography (OCT) is a hallmark of ARSACS, which distinguishes it from other ataxias. Many aspects of the pathogenesis of ARSACS are not clear and large series of Brazilian patients have not been published. OBJECTIVES: This thesis is divided in two studies, with the following objectives: Study 1 - To evaluate the clinical, genetic, neuroimaging and ophthalmological profile of Brazilian patients with ARSACS. Study 2 - To analyze qualitatively the retinal architecture of 28 ARSACS cases. METHODS: In the Study 1, we included 13 consecutive cases of spastic ataxia harboring two SACS variants and performed detailed neurological assessment, neuroimage study and ophthalmological evaluation, and applied scales to quantify ataxia severity. Brazilian patients phenotype was compared to the largest series published. The Study 2 investigated the retinal architecture of 28 ARSACS cases using fundoscopy and perifoveal spectral domain OCT scans. RESULTS: Study 1 - The phenotype of Brazilian patients with ARSACS is characterized in most cases by spastic ataxia with onset in the first decade of life. Abnormalities in neuroimaging and retinal architecture occurred in the majority. Study 2 - Patients with ARSACS presented specific findings in qualitative analysis of retinal architecture. We identified peripapillary striations, a papillomacular fold, the saw-tooth sign and foveal hypoplasia in OCT. CONCLUSIONS: Study 1 is the first to evaluate systematically the phenotype of ARSACS in a large Brazilian cohort and confirmed the importance of neuroimaging and OCT in the work-up of recessive ataxias. Study 2 revealed specific signs of ARSACS in qualitative analysis of retinal architecture and demonstrated ARSACS causes foveal hypoplasia, suggesting a neurodevelopmental component in its pathogenesis.